Patterns of contraceptive use among female undergraduates in the University of Ibadan, Nigeria (2010)
This study was conducted to determine pattern of contraceptives use among female undergraduates in the University of Ibadan, Nigeria. A descriptive cross- sectional study was conducted among female undergraduates resident on campus using self-administered questionnaires Overall, 425 female undergraduates between the ages of 15 and 30 years were interviewed. Only 28.7% of the respondents were sexually active and mean age at sexual debut was 19 years ±2.31 years. About 63.9% of the sexually active respondents had ever used some form of contraceptives mainly the condom and pills. Only (26.7%) of the sexually active respondents used a contraceptive at their last sexual encounter and contraceptive use was significantly higher (p<.05) among the older females’ contraceptive use among the sexually active female undergraduates of the University of Ibadan was not optimal although knowledge of various methods was high. Appropriate interventions are needed to encourage contraceptive use among sexually active female undergraduate